EFFECT OF THE JUICE OF GINGER RHIZOMES ON THE PHARMACOKINETICS OF SULFAMEZATHINE IN RATS - ., Purwantiningsih; Hakim, Lukman (INDONESIAN JOURNAL OF PHARMACY, 2003)
The rhizome of ginger (Zingiber officinale, Rosc.) has been widely consumed by people as food ingredient or a traditional drug. In the previous research there was evidence that the ginger juice influenced the pharmacokinetics of propranolol, a representative of drugs with high extraction ratio. The aim of this research is to study the effect of ginger juice on another high ER drug, sulfamezathine. To achieve the aim of this study, rats were divided into two groups to get the blood and urine data. The animals at the blood data group were divided into two groups. The group I (N=6) was given sulfamezathine (50 mg/kg BW) through intra peritoneal injection and the group II (N=6) was pretreated with the ginger juice orally (4 ml/kg BW) an hour prior to administration of sulfamezathine. The blood samples were withdrawn at various intervals after the drug administration. The unchanged sulfamezathine concentration was determined using a modified Bratton-Marshall method. From this blood data the values of Ka, Cmaks, Tmaks, Vdss, AUC, Cl and T1/2el were computed. Urine data was obtained by using two groups of rats with the same treatment as above. The sulfamezathine was counted from urine which accumulated for 24 hours to obtain the value of Fel. The results of this research showed that significant decreases in Cmaks (16.72%) and AUC (22.92%) values have occurred, with increasing values of Vdss (18.39%), ClT (38.29%), ClR (213.11%) and Fel 24 hours (128.58%) values. Key words : ginger rhizome, pharmacokinetics, sulfamezathine, rats